Assessing the Influence of the Flipped Classroom on Physical Education Students’ Engagement in Basketball Learning Activities - Wibowo, Cahyo; Nopiyanto, Yahya Eko; Raibowo, Septian; Insanistyo, Bayu; Kardi, Ipa Sari; Ibrahim; Rasyono; Defliyanto; Cs, Ansar (Physical Education Theory and Methodology, 2024)
Background. The flipped classroom approach has been gaining increasing attention across various educational domains, including physical education. Recent research has underscored the necessity for innovative strategies to enhance student engagement in physical education, particularly in basketball instruction. Objectives. This study aimed to investigate the influence of the flipped classroom approach on student engagement in Basketball instruction within the Physical Education, Health, and Recreation program at the University level. Materials and methods. The research method involved an experimental design using the static group comparison approach, where 62 students enrolled in physical education were divided into experimental and control groups. The experimental group received instruction through the flipped classroom approach, while the control group underwent conventional instruction, with the intervention lasting for seven weeks. A comprehensive engagement scale questionnaire was used as the research instrument. Data analysis techniques included descriptive analysis and independent samples t-test. Results. The research findings revealed significantly higher levels of engagement in the agentic, behavioral, emotional, and cognitive dimensions among students in the flipped classroom group compared to those in the conventional classroom group. This indicates that the flipped classroom approach has a considerable effect on student engagement in basketball instruction. Conclusions. The study’s results have confirmed the effectiveness of the innovative pedagogical strategy of the flipped classroom in fostering meaningful learning experiences and motivating students within the context of physical education.